Ties to the rest: autocratic linkages and regime survival - Oisin Tansey; Kevin Koehler; Alexander Schmotz (Comparative political studies, 2017)
The relationship between international linkages and the nature and survival of political regimes has gained increasing attention in recent years, but remains one that is poorly understood. In this article, we make three central contributions to our understanding of international linkage politics and autocratic regime survival. First, we introduce and develop the concept of “autocratic linkage,” and highlight its importance for understanding the international politics of autocratic survival. Second, we use event history analysis to demonstrate that autocratic linkage has a systematic effect on the duration of authoritarian regimes. Finally, we complement our quantitative analysis with a focused comparison of autocratic linkage politics in the Middle East. We show that variation in Saudi Arabian support for autocratic incumbents in the wake of the Arab Spring protests can be explained in significant part by variation in linkage relationships.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; autocratic regime survival; international linkage; Arab Spring; survival analysis